Joint Optimal Pricing and Ordering Decisions for Seasonal Products with Weather-Sensitive Demand - Hongyong Fu; Bin Dan; Xiangkai Sun (Discrete Dynamics in Nature and Society)
Retailers selling seasonal products often face the challenge in matching their inventory levels with uncertain market demand which is sensitive to weather conditions, such as the average seasonal temperature. Therefore, how to make the joint ordering and pricing decisions may help retailers to increase their profits. In this paper, we address the joint determination of pricing and ordering decisions in a newsvendor setting, where a retailer (newsvendor) sells the seasonal products and faces demand risk due to weather uncertainty. We show that the maximum expected profit function is continuous and concave, so the optimal solution to the retail price and order quantity exists and it is the one and only solution. In addition, we numerically investigate the impacts of related parameters on the retailer’s expected profit and the optimal pricing and ordering decisions and illustrate some useful management insights into the economic behavior of firms.